2013
DOI: 10.1007/s00508-013-0378-3
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Rubella in northeastern Turkey

Abstract: In spite of the active immunization programme commenced after 2006, rubella infection is still a risk in Turkey without discriminating the gender.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Also effectiveness of rubella mass vaccination it has also proven in other countries. [16][17][18] The increased trend of anti-rubella antibody with aging was shown in this study, which is maybe due to higher risk of disease or contact with virus with increase in age. Although this trend was not significant which could be due to the fact that the sample size of present study did not have enough power to show changes in trend.…”
Section: Discussionmentioning
confidence: 55%
“…Also effectiveness of rubella mass vaccination it has also proven in other countries. [16][17][18] The increased trend of anti-rubella antibody with aging was shown in this study, which is maybe due to higher risk of disease or contact with virus with increase in age. Although this trend was not significant which could be due to the fact that the sample size of present study did not have enough power to show changes in trend.…”
Section: Discussionmentioning
confidence: 55%
“…Similar findings were reported in Sweden, with a seroprevalence of 95.8% among 41637 individuals after 22 years of an MMR immunization program (10). Akkoyunlu et al in northeastern Turkey revealed 73% (11) and Calimeri et al in Italy measured 85.8% (12) immunity in their studies. According to the cost-effectiveness analysis performed, systematic vaccination costs three to four times less than elective vaccination (13).…”
Section: Discussionmentioning
confidence: 82%
“…In a study in Brazil, positive antibody titer was reported as 76% ( 23 ). Other studies in Turkey ( 24 ), India ( 25 ), Syria ( 26 ), Sudan ( 27 ) and Burkina-Faso ( 28 ) reported anti-rubella antibody titers as 81.8%, 87.2%, 85.6%, 95.1% and 95%, respectively. In Iran, several studies were conducted in different age groups before national vaccination in 2003 and reported immunity of women of reproductive age as 78%-94% ( 29 - 32 ), which showed high susceptibility of this age group to rubella and potential CRS in infants born of these women.…”
Section: Discussionmentioning
confidence: 95%